2012
DOI: 10.1002/ffj.3105
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the aromatic profile of the Quebranta variety of Peruvian pisco by gas chromatography–olfactometry and chemical analysis

Abstract: Twenty‐one commercial pisco samples made with Quebranta grapes from four different geographical areas in Peru have been evaluated by gas chromatography–olfactometry (GC‐O) and chemical quantitative analysis. The GC‐O study revealed that the Peruvian pisco from the Quebranta grape variety has a relatively simple aroma profile formed by 22 odorants, all of which could be identified. Most of the odorants are fermentation related, while guaiacol, β‐damascenone, geraniol and linalool come from the grape. The chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…The other 43 compounds were determined by the GC‐MS analysis of extracts obtained by solid phase extraction from diluted pisco, and the results are given in Table . Results for the calibration of many of these compounds are given in previous papers . However, 30 of the analysed compounds have been calibrated in this study and their calibration data are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The other 43 compounds were determined by the GC‐MS analysis of extracts obtained by solid phase extraction from diluted pisco, and the results are given in Table . Results for the calibration of many of these compounds are given in previous papers . However, 30 of the analysed compounds have been calibrated in this study and their calibration data are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The temperature program was as follows: 40 °C for 3 min, then raised at 6 °C/min to 75 °C, and at 9 °C/min to 220 °C, and finally was held at 220 °C for 10 min. Complete information about the calibration of some of the compounds analysed in this study is provided in previous papers …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations